The impact of financial leverage on farm technical efficiency during periods of price instability - Gadanakis, Yiorgos; Stefani, Gianluca; Lombardi, Ginerva Virginia; Tiberti, Marco (My University, 2020)
Purpose: The purpose of this paper is to provide empirical evidence on the relationship between capital structure and technical efficiency (TE) for Italian cereal farms during the 2008–2014 period. Emphasis is given in the understanding of the relationship between the level of financial leverage for cereal farms and their production performance. Design/methodology/approach: The methods employed in this research article are based on non-parametric techniques in order to derive TE estimates for a sample of Italian cereal farms based on available Farm Accountancy Data Network data to explore in depth the relationship amongst the financial exposure of the sector and the capacity to utilise an efficient and effective production technology. Furthermore, subsidies are considered in the model as a non-discretionary variable and therefore, as an input that farmers cannot directly influence within the production function. Hence, the non-discretionary Data Envelopment Analysis model is a more appropriate framework since it is not penalising farms at a lower level of Pillar I payments when benchmarked with farms that receive a higher level of payments. Findings: The results show that significant improvements could be achieved for most of the farms in the sample by improving production and management practices. Furthermore, results provide an empirical support of the adjustment theory by showing a negative impact of debt to asset ratio to TE. Originality/value: This research article provides a first insight on the evolution of the Italian cereal farms debt-TE relationship in periods where high price instability has been observed.
Keywords: Adjustment Theory; Financial Leverage; Technical Efficiency; Capital Structure; Expenditure capacity; Price instability